The Problem of Student Disengagement: Struggle, Escapism and Nietzsche’s Birth of Tragedy - Yacek, Douglas W.; Jonas, Mark E. (Philosophical Inquiry in Education, 2019)
Numerous studies have shown that secondary and college students are increasingly apathetic and disengaged from their schooling. The problem of student disengagement is not confined to under-represented socioeconomic groups; it is found across the country—in cities, suburbs, and rural communities; in wealthy schools and poor schools; in public schools and charter schools; in majority white schools and those composed largely of students of color. In this essay, we argue that Friedrich Nietzsche’s Birth of Tragedy contains crucial pedagogical and conceptual resources for responding to this widespread problem. The conception of “Dionysian pessimism” Nietzsche advances in this early work and its relationship to the escapist, “Alexandrianism” he observes in late 19th century German education are relevant to the contemporary problem of student disengagement, we argue, because they address head on the reality of struggle in students’ academic experiences and can potentially explain the disengagement they experience when they fail to acknowledge, accept and even embrace the struggle of education. When struggle is seen as something to be avoided and endured only for the sake of later academic and career success, as it often is, Nietzsche argues that apathy, disengagement and even resentment can result. Thus, while Nietzsche’s diagnosis is rooted in an analysis of his own culture and time, this essay hopes to show that it has the potential to speak to important practical issues in contemporary education.